The Effect and Safety of Dexmedetomidine Administration on Mother and Foetus/Neonates During General Anaesthesia in Caesarean Section: A Randomised Controlled Trial - Zhiqiang Yu; Yan Liu; Fangqi Duan; Qian Li; Dong Yan; Li Zhang; Zhuangzhuang Wang; Minyu Zhang; Qi Zhao (Journal of Investigative Surgery)
Purpose This study aimed to assess the safety of dexmedetomidine administration to mothers, fetuses, and neonates during general anesthesia in cesarean section (CS).Patients and methods A total of 60 parturients scheduled for elective CS under general anesthesia were randomly divided into anesthesia in groups (DEX1 and DEX2) and control (C) groups. Groups DEX1 and DEX2 were induced with dexmedetomidine (induction, 0.4 µg/kg; maintenance, 0.4 µg/kg·h) and dexmedetomidine (induction, 0.6 µg/kg; maintenance, 0.6 µg/kg·h), respectively, until birth. Equivalent volumes of normal saline were administered in group C. Anesthesia was induced with propofol and rocuronium in all groups. The mean arterial blood pressure (MAP) and heart rate (HR) of parturients were monitored and recorded; fetal HR was monitored using color doppler ultrasound. The blood gas analysis from the umbilical artery (UA) and umbilical vein (UV), along with the HR, Apgar score and Neurologic Adaptive Capacity Scores (NACS) of neonates, were recorded.Results Maternal MAP at intubation/skin incision, maternal HR at intubation/skin incision and delivery were significantly lower in groups DEX1 and DEX2 than in group C, no significant differences were observed between groups DEX1 and DEX2. No significant differences were observed in fetal HR, UA and UV blood gas analyses, Apgar score and NACS of neonates in the three groups.Conclusion Intravenous 0.4 or 0.6 µg/kg doses of dexmedetomidine with propofol for general anesthesia in CS is beneficial for inhibiting the maternal stress response induced by intubation/skin incision and delivery without significant adverse effects on fetuses or neonates. Our findings suggest that dexmedetomidine is safe for mothers, fetuses, and neonates in obstetric general anesthesia.